Il grido di Abacuc. La questione ecologica alla luce delle istanze del giusnaturalismo cristiano contemporaneo (Stato, Chiese e pluralismo confessionale, 2014)
Contributo sottoposto a valutazioneSOMMARIO: 1. Ecologia e religioni. Il rapporto uomo-natura nella visione escatologica dell’unità tra creazione e storia. Critiche all’antropocentrismo cristiano e derive panteistiche - 2. Chiesa cattolica e questione ecologica. Il nuovo imperativo categorico: l’ecologia umana nel Magistero pontificio post-conciliare - 3. L’ecologia umana come preoccupazione comune alle principali Chiese cristiane- 4. Riflessioni sulla causa del disastro ecologico umano-ambientale: la soluzione del problema nella natura giuridica della persona umana. Abstract In the present work – based on a suggestion coming from the Scriptures- we investigated the relashionship between human disobedience to the commands of God and the revolt of the creation that manifests in the natural upheavals.Become one of the most challenging cultural issues for the modern world, even the religious faiths reflect on the ecological question, because it regards the deep relashionship between man and all over the world created.But the ebraic-christian monotheism develops an ontological doctrine of creation purposeful orientated toward redemption.The christian revolution is that man is the centre of the universe and ontological different from the others creatures, in respect of which is vested of responsability. But humanity power has become limitless, consequently new methaphisic and religious tendences offer a vision of nature deified (Deep ecology-Gaia), in which man depersonalized is privated of moral and legal responsibility.In post-conciliar magisterium Catholic Church addresses the ecological problem interpreting it as an anthropological question.It’s useless taking care of the environment without priority to the human rights. This is one of the most important principle of Social Doctrine of Catholic Church. The ecological disaster is an human fault, and the solution of this emergency is a revaluation of natural law, a duty for the common man and the jurist.